Genetic variation relevant for the conservation of the narrow endemic Senecio carbonensis (Asteraceae) from the southern Andes - Fernández, Martina (2011)
We studied morphological variation, reproductive biology and genetic structure of Senecio carbonensis, a narrow endemic from high elevations of the southern Andes, and compared it to Senecio peteroanus, a closely related widespread congeneric species. Using ANOVAs and discriminant analysis we showed that populations of S. carbonensis were more similar to each other in their morphology, had comparatively limited reproductive capacity and presented lower plant density and more reduced plant cover than populations of S. peteroanus. Similar high genetic variation was found at the population and species level in both species, based on isozyme variation at 14 and 11 putative gene loci that were resolved in S. carbonensis and S. peteroanus, respectively. The two species were genetically distinct. However, the small genetic distance between populations of each species suggests that either they were recently founded and that genetic drift did not have time to promote divergence, or that its effects are masked by significant current gene flow. These results show that ecological and reproductive characteristics of S. carbonensis may limit its extension and abundance. In contrast, high genetic variation at the population level is probably favored by self-incompatibility. Despite the restricted geographical distribution and low plant density of S. carbonensis populations, genetic characteristics do not seem to be limiting their long-term persistence. This information suggests that populations of S. carbonensis are not at risk of extinction as a result of genetic factors, although it is important to study and monitor population dynamics to further assess the degree of recruitment through time.